2015
DOI: 10.1016/j.jnucmat.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Fission product partitioning in aerosol release from simulated spent nuclear fuel

Abstract: a b s t r a c tAerosols created by the vaporization of simulated spent nuclear fuel (simfuel) were produced by laser heating techniques and characterised by a wide range of post-analyses. In particular attention has been focused on determining the fission product behaviour in the aerosols, in order to improve the evaluation of the source term and consequently the risk associated with release from spent fuel sabotage or accidents. Different simulated spent fuels were tested with burn-up up to 8 at. %. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…For example, we have identified Cs 2 MoO 4 in the inhalable aerosol fraction produced by reaction of CsI and Mo in air after a short thermal transient generated by a laser pulse and concluded that it was formed by condensation of the gaseous phase [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, we have identified Cs 2 MoO 4 in the inhalable aerosol fraction produced by reaction of CsI and Mo in air after a short thermal transient generated by a laser pulse and concluded that it was formed by condensation of the gaseous phase [8].…”
Section: Introductionmentioning
confidence: 99%